2022
DOI: 10.1186/s43066-021-00164-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of linear endosonography in patients with unexplained biliary dilatation and negative MRCP, with predictors for detection of neoplastic lesions

Abstract: Background and study aims Unexplained biliary dilatation (UBD) frequently represents a diagnostic dilemma. Linear endosonography (EUS), with its close proximity to the pancreaticobiliary system and the ability for tissue acquisition, could have a role in revealing etiologies of UBD particularly in the context of negative other non-invasive modalities. However, in such patients, the decision for this semi-invasive procedure is usually debatable and often needs justification. Thus, we aimed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Women made up the majority of the patients, who had a sex ratio of M/F: 0.2 and age range of 28 to 80 years. Also, many previous studies reported close results (6,7,10) . In contrast Phan et al (8) reported that the majority of patients (63.5%) were men, and at diagnosis, the average age was 64.6 ± 14.7 years.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Women made up the majority of the patients, who had a sex ratio of M/F: 0.2 and age range of 28 to 80 years. Also, many previous studies reported close results (6,7,10) . In contrast Phan et al (8) reported that the majority of patients (63.5%) were men, and at diagnosis, the average age was 64.6 ± 14.7 years.…”
Section: Discussionsupporting
confidence: 54%
“…Also, Ding et al (7) reported that the most common symptoms were abdominal pain (60.9%), followed by Jaundice (31.3%), fever (11.3%), nausea and emesis (5.2%), and weight loss (3.5%). However, Atalla et al (10) reported that upper abdominal pain and jaundice were the two most typical presentations in their cohort (n = 43, 70.5% each) (n = 10, 16.4%).…”
Section: Discussionmentioning
confidence: 82%